Estimating the marginal value of agricultural irrigation water: A methodology and empirical application to the Berg River Catchment - Muller, Jacob (School of Economics, 2017)
This study aims to facilitate effective and efficient intersectoral water allocation policy in South Africa, where limited water supplies are increasingly constraining necessary economic development. The study develops an economic model of irrigated agricultural production that recognises the multi-output nature of irrigated agriculture as well as the institutional setting in which commercial irrigation water is allocated in South Africa. The model is then used to econometrically estimate the marginal value of commercial irrigation water in the Berg Water Management Area (WMA), using a Translog functional form, Tobit censored regression model, including controls for heterogeneity, and accounting for heteroscedasticity. The estimates are obtained for 16 irrigated crops in the region and range from an overall mean of 4.84 R/m³ for peaches to 0.14 R/m³ for wheat, but vary significantly between sub-regions and according to soil productivity as well as between crops. Furthermore, the estimates differ substantially from the average value of production per m³ of irrigation water, reflecting a revenue-water elasticity that differs from unity for all crops. The results imply that potential efficiency gains are possible from the intersectoral reallocation of water away from agriculture. A further implication is that reallocation within the agricultural sector would be most efficiently undertaken by farmers themselves, due to the large number factors that affect irrigation water productivity but are unobservable by policymakers or are difficult to account for in the formulation of policy.